PEMBERDAYAAN EKONOMI LOKAL MELALUI PENGOLAHAN HASIL PERTANIAN BAGI IBU RUMAH TANGGA SEKITAR UIN SATU TULUNGAGUNG: LOCAL ECONOMIC EMPOWERMENT THROUGH PROCESSING AGRICULTURAL PRODUCTS FOR HOUSEWIVES AROUND UIN SATU TULUNGAGUNG - Risdiana Himmati; Lativa Hartiningtyas; )Adinda Putri Yesa Isnawati (LPPM Universitas Abdurrab, 2025)
This community service program aims to increase family income, especially for housewives, through training in banana chip processing. This training teaches the technique of processing bananas into crispy chips with high economic value, utilizing the abundant potential of bananas in the surrounding area. Using the Asset Based Community Development (ABCD) method, this program focuses on community empowerment by utilizing local assets and enhancing production skills. In addition to technical training, participants also receive guidance in product marketing and packaging aspects. Through mentorship sessions from marketing experts, housewives were given insights into digital marketing strategies and the importance of product branding. As a result, the participants successfully improved product quality, enhanced packaging, and marketed their products through various channels, including social media. This program has a positive impact on increasing the income of the participants' families, creating new business opportunities, and expanding the market. With a comprehensive approach, this program is expected to create economic sustainability at the local level and improve the welfare of housewives.